Knowledge of Helminthiasis of People Living in Slum Areas of Bandung District, Indonesia - Faridah, Lia; Fauziah, Nisa; Adrizain, Riyadi (Majalah Kedokteran Bandung, 2021)
Among the most prevalent infections worldwide, Soil-Transmitted Helminth (STH) infection is the one that affects the poorest and most deprived populations. Data from the WHO shows that more than 1.5 billion people are affected by soil-transmitted helminth diseases globally. In 2010, it was estimated that 819.0 million, 464.6 million, and 438.9 million people around the world were infected with Ascaris lumbricoides, Trichuris trichiura, and hookworms (Ancylostoma duodenale and Necator americanus), respectively, with the Southeast Asia as the region with the highest prevalence of STH. Children’s awareness and knowledge of helminthiasis are essential to reduce the STH infection prevalence. Unfortunately, evaluation on children’s understanding of helminthiasis is still scarce. This study was intended to measure children's knowledge of STH infections and its prevention, especially prevention measures at home, in Bandung District, Indonesia. This study was conducted in March 2021 on 506 children who lived in 15 different subdistricts in Bandung District. Data were collected through a questionnaire that was used for face-to-face interviews with the children. All data were recorded in RedCap apps for further analysis. It was demonstrated in this study that children in Bandung District generally have low-to-medium knowledge on helminthiasis prevention, symptoms, and treatment (85%). Thus, there is an urgent need for an education program on helminthiasis to complement the deworming measures conducted by the local government.